DEVELOPMENT OF INSTRUCTIONAL MATERIALS FOR EARTHQUAKE DISASTER PREVENTION AND ITS EVALUATION - MATSUDA, Toshiki; MORIKAWA, Hitoshi; TAKAMURA, Saori (Environmental systems research, 2005)
Many projects of the education for the earthquake disaster prevention have been carried out considering the experiences obtained through the 1995 Hyogoken Nanbu earthquake. However, such projects were not enough to educate the people over eighteen years old, because of their less motivation, for example. We, thus, developed web-based instructional materials as a tool to improve their comprehension of the earthquake disaster. The materials are designed for any people to study the topics about the earthquake and disaster for themselves. For the design of the materials, we paid attention to some points: they can study anytime and anywhere on the web and confirm their understanding through the review exercises. It is expected that the effective learning is advanced by these points. Some subjects tried to use the materials and their comprehension were evaluated by some exercises. From this, we verified quantitatively the effect of learning by means of the materials.